Role of pemetrexed in advanced non-small-cell lung cancer: meta-analysis of randomized controlled trials, with histology subgroup analysis - Al-Saleh, K. (Multimed Inc., 2012)
PURPOSE: Platinum-based regimens represent the standard first-line treatment for non-small-cell lung cancer (nsclc). However, newer data have established a role for pemetrexed in the treatment of this disease. Such data suggest that histology represents a determining factor in the selection of treatment. METHODS: We undertook a systematic review of the literature for randomized controlled trials that compared the efficacy of pemetrexed with that of other treatments in advanced nsclc. Data and study quality were assessed according to published guidelines. RESULTS: We identified five trials that compared pemetrexed with other treatments or with placebo. Overall survival for patients treated with pemetrexed was superior to that with other treatments: hazard ratio (hr): 0.89; 95% confidence interval (ci): 0.80 to 0.99. The survival benefit was limited to patients with non-squamous histology: hr: 0.82; 95% ci: 0.73 to 0.91. Pemetrexed was inferior to other chemotherapy options in patients with squamous histology: hr: 1.19; 95% ci: 0.99 to 1.43. CONCLUSIONS: Compared with other chemotherapy agents, pemetrexed is more effective for the treatment of nsclc in patients with non-squamous histology.